2019
DOI: 10.1111/anae.14931
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a low‐dose naloxone infusion on the incidence of respiratory depression after intrathecal morphine administration for major open hepatobiliary surgery: a randomised controlled trial

Abstract: Summary Intrathecal morphine is an analgesic option for major hepatopancreaticobiliary procedures but is associated with a risk of respiratory depression. We hypothesised that a postoperative low‐dose naloxone infusion would reduce the incidence of respiratory depression without an increase in pain scores. Patients scheduled for major open hepatopancreaticobiliary surgery and who were receiving 10 μg.kg−1 intrathecal morphine were eligible for inclusion. Patients were allocated randomly to receive a postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…This higher concentration of morphine would require a higher concentration of antagonist, compared to the lower concentrations of morphine in the respiratory center. Based on this differential effect, an approach can be to administer continuous naloxone routinely to prevent respiratory depression but maintain analgesia [ 44 , 45 ]. However, this strategy requires further research regarding effectiveness and side effects.…”
Section: Discussionmentioning
confidence: 99%
“…This higher concentration of morphine would require a higher concentration of antagonist, compared to the lower concentrations of morphine in the respiratory center. Based on this differential effect, an approach can be to administer continuous naloxone routinely to prevent respiratory depression but maintain analgesia [ 44 , 45 ]. However, this strategy requires further research regarding effectiveness and side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Uhlmann et al [ 6 ] demonstrated that mild to moderate pain after parathyroidectomy may render patients ineligible for postoperative recovery programs. A previous study showed that two-thirds of patients undergoing parathyroidectomy require narcotic analgesics to relieve postoperative pain on the first day after surgery, whereas the incidences of postoperative nausea, vomiting and apnea or respiratory depression also increase [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following intrathecal morphine administration in patients with major hepatopancreaticobiliary surgery, a low-dose naloxone infusion postoperatively decreases the incidence of respiratory depression at the expense of a small increase postoperative pain. 52 This study provides valuable information for the anesthesiologists using intrathecal administration of opioids as the main pain management modality for live liver donors.…”
Section: Liver Transplantationmentioning
confidence: 99%